The role of arbuscular mycorrhizal fungi in nonnative plant invasion along mountain roads - Clavel, Jan; Lembrechts, Jonas; Alexander, Jake; id_orcid:0 000-0003-2226-7913; Haider, Sylvia; Lenoir, Jonathan; Milbau, Ann; Nuñez, Martin A.; Pauchard, Aníbal; Nijs, Ivan; Verbruggen, Erik (New Phytologist, 2021)
ISSN:0028-646X ISSN:1469-8137